Educación para la Paz en Colombia: una búsqueda más allá del discurso (2013)
The fast changes in today’s society require to think over the education that is forming children and youth. The warlike conflicts, hunger, inequality, injustice, among many other socioeconomic phenomena only show the change in the scale of values and the supremacy of violence as a response to the conflict. In the Colombian social and political framework, this change is not only necessary but urgent. This change starts with understanding peace as something else than the end of armed conflict, identifying other types of violence that kill silently more people than the same bullets do. This article is part of the Project of Reflection around building peace and citizenship presented by the Center for Studies in Education of the University of Santo Tomas, Bucaramanga to the lectures of Andres Bello Integration - Association of Universities of Latin America and the Caribbean for Integration (AUALCPI). The aim of this article is to point out the need to understand the violence in its complexity by recognizing the contributions of Joan Galtung in studies on violence and peace and making a commitment to peace education as the most suitable way to promote a real change in the process to build otherness. The challenge in our country is to start from education and specifically from school to train supportive, critical but non-violent individuals, and thus contribute to the existence of a culture of peace.